Cardiovascular Health Behaviors and Risk Factors Among Argentine and American University Students - Gabriella Lynne Smith; Gina Fitzgerald; Don Thompson (International Journal of Public Health Science (IJPHS), 2014)
Cardiovascular disease is the leading cause of death in adults in both theUnited States and Argentina. Scientific literature has consistently shown the effects of behaviors and risk factors on cardiovascular health; however, few have investigated cardiovascular behaviors and risk factors in early adulthood. We assessed the associations between main cardiovascular behaviors and cardiovascular risk factors among 594 young adults in a crosscultural analysis between the United States and Argentina through a webbased survey and vital statistics measurements. We tested our data through principle component analysis, bivariate correlations, and independent sample T-tests.After thorough analysis we saw that, cross culturally, correlations exist between cardiovascular risk factors and behaviors that are consistent in both populations. Health habit, health knowledge, health history and BMI are all significantly correlated with mean arterial pressure. T-tests showed that population groups with a higher risk factor mean also had lower behavior means, indicating that populations with poor cardiovascular behaviors correlate with an accumulation of cardiovascular risk factors. In conclusion, young adults with low prevalence of cardiovascular health behaviors have low prevalence of cardiovascular health risk factors.